Performance evaluation of premixed burner fueled with biomass derived producer gas - P. Punnarapong (2018)
© 2016 The Authors. Published by Elsevier Ltd. Energy consumption of liquefied petroleum gas (LPG) in ceramic firing process accounts for about 15-40% of production cost. Biomass derived producer gas may be used to replace LPG. In this work, a premixed burner originally designed for LPG was modified for producer gas. Its thermal performance in terms of axial and radial flame temperature distribution, thermal efficiency and emissions was investigated. The experiment was conducted at various gas production rates with equivalence ratios between 0.8 and 1.2. Flame temperatures of over 1200 °C can be achieved, with maximum value of 1260 °C. It was also shown that the burner can be operated at 30.5-39.4 kW th with thermal efficiency in the range of 84 - 91%. The maximum efficiency of this burner was obtained at producer gas flow rate of 24.3 Nm 3 /h and equivalence ratio of 0.84.